Terumbu Karang Taman Wisata Perairan Pulau Pieh Sumatera Barat - Dian Sutono HS; Syamsul Bachri Lubis (Jurnal Airaha, 2018)
The Marine Conservation Area (MCA) of the Marine Tourism Park of Pieh and the Surrounding Islands, consists of Bando Island, Pieh Island, Air Island, Toran Island and Pandan Island with covering of ​​39,900 Ha wide. Geographically Pieh Island is at coordinates 00⁰ 45’ 10" - 01⁰ 03’ 08" LS / 99⁰ 59’ 36" - 100⁰ 59’ 28" BT, and administratively falls within the Padang Pariaman District, Pariaman City and Padang City. The research was carried out in the waters of the core zone of the MCA Toran Island. Pieh Island at coordinates 01⁰ 01 '55 "- 01⁰ 03' 02" LS / 100⁰ 09 '36 "- 100⁰ 11' 02" BT. With the LIT (Line Intercept Transect) method using a 50 meters long transect with the rope drawn parallel / horizontally. stretch of coral reefs at six points of the observation station. The results shown the percentage of live coral cover ranged from 20.94% - 35.00% (bad - moderate category) with an average value of 25.93% (medium category). The diversity index value (H ') ranges from 1.76 - 3.16 (low - high category), with an average value of 2.44 (medium category). The uniformity index (E ') value is generally classified as a high category (stable community) ranging from 0.77 - 1.00 with an average value of 0.88 (medium category). While the dominance index (C ') does not show the extreme conditions of one species against the other species, this is indicated by the dominance index value of less than 0.5 (low category), which ranges from 0.05 - 0.42 with an average value 0.24 (low category).